1978
DOI: 10.1002/pol.1978.170161123
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR spectroscopic study of epoxidized 1,4‐polyisoprene and 1,4‐polybutadiene

Abstract: Partly epoxidized cis‐ and trans‐1,4‐polyisoprenes and cis‐and trans‐1,4‐polybutadienes were prepared, and their 13C NMR spectra examined. All the prominent resonances in the spectra of the epoxidized polymers were assigned by using lanthanide shift reagent and off‐resonance decoupling experiments. A 13C NMR method of quantitative assessment of the epoxide content was developed following determination of relative spin‐lattice relaxation time (T1) and nuclear Overhauser effect (NOE) parameters of the various ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 9 publications
8
35
0
Order By: Relevance
“…In HTPB, cis and trans double bonds had their signals at 129 ppm, but as the epoxidation reaction progressed, additional signals appeared at 56 ppm and 58 ppm, which were pertinent to cis and trans epoxy, respectively. The obtained results are similar to the results obtained by Gemmer and Golub [29] . Focusing on the 114 ppm and 141 ppm regions in the 13 CNMR spectra, we found that vinyl carbons remained unchanged due to their low electron density.…”
Section: Characterization Of the Epoxidized Polymerssupporting
confidence: 82%
See 2 more Smart Citations
“…In HTPB, cis and trans double bonds had their signals at 129 ppm, but as the epoxidation reaction progressed, additional signals appeared at 56 ppm and 58 ppm, which were pertinent to cis and trans epoxy, respectively. The obtained results are similar to the results obtained by Gemmer and Golub [29] . Focusing on the 114 ppm and 141 ppm regions in the 13 CNMR spectra, we found that vinyl carbons remained unchanged due to their low electron density.…”
Section: Characterization Of the Epoxidized Polymerssupporting
confidence: 82%
“…These signals were respectively, shifted to about 2.9, 2.7, 2.5, and 3.0 ppm in the epoxidized HTPB. Of course, we did not observe vinyl epoxy in the 1 HNMR, which was due to the lower reactivity of vinyl bonds in comparison to cis and trans double bonds [29] . This indicates that vinyl double bonds are rarely epoxidized.…”
Section: Characterization Of the Epoxidized Polymersmentioning
confidence: 94%
See 1 more Smart Citation
“…Note added in proo[: An attractive alternative to reaction (5) which can account for the loss of vinyls and the accompanying formation of methyls, with no apparent loss of vinylenes, in polybutadienes with low vinyl contents, is reaction (6).…”
Section: And Discussionmentioning
confidence: 99%
“…The assigning of cis, trans and vinyl epoxy groups was based on data reported by Akcelrud et al [5], Zuchowska [9] and Gemmer and Golub [23]. By the comparison of the peak areas for epoxy protons at 2.7 and 3.0 ppm with the unreacted one, it was found that the absorption at 2.7 ppm was related to the trans, whereas the one at 3.0 ppm was related to the cis epoxy protons, respectively (Fig.…”
Section: Characterization Of the Epoxidized Htpbmentioning
confidence: 99%